CBR Mapping Prediction from 2D Resistivity Imaging Using Regression Following Archie’s Formula - Mohamed El Basri; Hasnaa Harmouzi; Lahcen El Basri; Mohamed Mastere; Ibrahim Ouchen; Bouchta El Fellah; Brahim Benzougagh (Iraqi Geological Journal, 2024)
Indirect geophysical methods are increasingly associated with direct underground methods in investigating the subsurface to address environmental and geotechnical problems and reduce the cost of underground studies. These methods make it possible to explore large areas with acceptable precision, time, and cost. The present study combines the electrical resistivity method with the California Bearing Ratio for exploring an area located west of the Nouakchott port in Mauritania. The study aims firstly to verify that the thickness of the backfill layer must be less than 2 m throughout the entire study area and secondly to map areas with low California Bearing Ratio values (<80%) indicating substandard backfill compaction using 2D Electrical Resistivity Tomography imaging survey and regression. The measured Electrical Resistivity values exhibit a good nonlinear regression with California Bearing Ratio, following Archie's equation. A map of California Bearing Ratio variation was derived from the Electrical Resistivity values, indicating the distribution and variation of soil strength in the study area. The results revealed that the backfill layer did not meet the standards, with approximately 35% of the total area having a California Bearing Ratio value below 80%. The areas with poor compaction requiring treatment were primarily located in the southern sector, followed by the middle and eastern sectors.